Dosimetric analysis of Deep Inspiratory Breath-hold technique (DIBH) in left-sided breast cancer radiotherapy and evaluation of pre-treatment predictors of cardiac doses for guiding patient selection for DIBH. (March 2021) - Ferdinand, Soujanya; Mondal, Monidipa; Mallik, Suman; Goswami, Jyotirup; Das, Sayan; Manir, Kazi S.; Sen, Arijit; Palit, Soura; Sarkar, Papai; Mondal, Subhayan; Das, Suresh; Pal, Bipasha
Highlights: DIBH results in cardiac sparing in left sided breast cancer radiotherapy. Heart volume in field and maximum heart distance are predictors of cardiac sparing. Thresholds of these anatomical predictors can help to select patients for DIBH. Abstract: Introduction: The risk of radiotherapy-associated cardiovascular disease has been a concern for decades in breast cancer survivors. The objective of our study is to evaluate the dosimetric benefit of Deep Inspiratory Breath-hold technique (DIBH) on organs-at-risk (OAR) sparing in left-sided breast cancer radiotherapy and to find out pre-treatment predictors of cardiac doses for guiding patient selection for DIBH. Material and methods: Pre-radiotherapy planning CT scans were done in Free Breathing (FB) and in DIBH [using Active Breathing Coordinator system (ABC™)] in 31 left sided breast cancer patients. 3DCRT plans were generated for both scans. Comparison of anatomical and dosimetric variables were done using paired t test and correlation was evaluated using Pearson correlation. Linear regression was used to get independent predictors of cardiac sparing and Receiver Operating Characteristic (ROC) curve analysis was done to find out the specific threshold of the predictors. Results: There was a 39.15% reduction in mean heart dose in DIBH compared to FB (2.4 Gy vs 4.01 Gy) (p < 0.001), 19% reduction in maximum Left Anterior Descending (LAD) dose and a 9.9% reduction in ipsilateral lung mean dose (p = 0.036) with DIBH. A significant correlation was observed between reduction in Heart Volume in Field (HVIF) and Maximum Heart Depth (MHD) with reduction in mean heart dose. Reduction in HVIF (ΔHVIF) independently predicted cardiac sparing. Conclusion: DIBH leads to significant reduction in OAR doses and is suggested for all patients of left-sided breast cancer undergoing radiotherapy. However, HVIF and MHD predicted for cardiac sparing and threshold criteria of ΔHVIF and ΔMHD may be used by centres with high workload to select patients for DIBH.